Soundscapes, soundtracks: Brazilian sound portraits (Per Musi, 2013)
This paper departs from the following assumptions 1) music is a prominent part of the soundscape (SCHAFER, 2001) and likewise, the soundscape interferes with compositional processes and the development of the aesthetical taste, 2) pieces of music broadcasted in the media are constituents of everyday life, since music itself produces habits and models of behavior. An analysis of these discrete elements could contribute to understand how social dynamics of cultures occurs, beyond the stereotyped and naive approaches.